Strengthening Community Capacity for Homestay Development in Mandalika Special Economic Zone, Indonesia - Kanom; Srilian Laxmiwaty Dai; Damianus Sonny Lamoren; Nur Afiah; Firman Koma Febdilan; Syul Rosli Sanam (Faculty of Economics and Business, University of Mataram, 2026)
This study examines the process of strengthening community capacity in tourism accommodation management within the context of homestay development in the Mandalika Special Economic Zone, Indonesia. As a government-driven tourism destination, Mandalika has experienced rapid infrastructure expansion, creating new opportunities for local communities to participate in tourism through homestay (Sarhunta) programs. However, the effectiveness of capacity-building initiatives in supporting sustainable community-based accommodation remains unclear. This research adopts a qualitative case study approach, supported by surveys, observations, and document analysis, to evaluate the effectiveness of training programs and identify key challenges faced by homestay operators. The findings reveal that capacity-building initiatives have been moderately effective in improving technical skills, particularly in housekeeping and basic hospitality services. However, significant gaps persist in managerial, adaptive, and strategic competencies, including financial management, digital marketing, and market responsiveness. The study identifies a critical capacity utilization gap, where knowledge gained through training is not effectively translated into practice. Furthermore, four interrelated dimensions of community capacity are proposed: technical, managerial, adaptive, and collaborative capacity. The results suggest that current capacity-building approaches remain fragmented and insufficient to support long-term business sustainability. This study contributes to the literature by offering an integrated framework for community capacity in tourism accommodation and highlighting the need for a shift from short-term training toward continuous, system-based capacity development. The findings provide practical implications for policymakers and stakeholders in designing more effective and inclusive tourism development strategies.